2012
DOI: 10.1038/hr.2011.227
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a single session of aerobic walking exercise on arterial pressure in community-living elderly individuals

Abstract: Several studies have demonstrated that one exercise session (ES) on a cycloergometer or ergometric treadmill causes a reduction in blood pressure (BP). However, there are few similar studies on walking, which is the exercise modality most available to the elderly. We investigated the immediate and 24-h effects of walking on BP in independent, community-living elderly individuals. Volunteers participated in a single ES and resting control session (CS). Before and after each session, BP was measured by auscultat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
(37 reference statements)
1
4
0
2
Order By: Relevance
“…These findings highlight the importance of regular cardiac walking among patients with hypertension. These findings are substantiated by the study conducted by Lima et al which revealed that there were immediate 14 mmHg and 12 mmHg reduction in systolic BP and 4 mmHg in diastolic BP after the exercise session for 5 days, which were statistically significant at p<0.05 and p<0.01, respectively [4]. Further, the above findings were supported by the study conducted by Warner and Louis on the effect of 30 minutes walking on BP for 5 days a week.…”
Section: Discussionsupporting
confidence: 80%
“…These findings highlight the importance of regular cardiac walking among patients with hypertension. These findings are substantiated by the study conducted by Lima et al which revealed that there were immediate 14 mmHg and 12 mmHg reduction in systolic BP and 4 mmHg in diastolic BP after the exercise session for 5 days, which were statistically significant at p<0.05 and p<0.01, respectively [4]. Further, the above findings were supported by the study conducted by Warner and Louis on the effect of 30 minutes walking on BP for 5 days a week.…”
Section: Discussionsupporting
confidence: 80%
“…33,44,54,57,66,67 Three studies included both medicated and nonmedicated patients with hypertension. 41,47,65 Exercise Characteristics Exercise sessions lasted on average ≈30 to ≈50 minutes. Different modalities of exercise were analyzed, including aerobic, 25,[32][33][34][35][36][37][39][40][41][42][43][45][46][47]50,[52][53][54][55][57][58][59][60]64,66,67 resistance, 32,38,44,49,51,56,[61][62][63]65 and combined aerobic and resistance exercise.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The existence of post-exercise hypotension, or decrease in BP, has been confirmed in both normotensive and hypertensive participants, both directly after and up to 24 h after increased activity. 44-46 In addition, care should also be taken in recording BP measurements during the same time of the day, with participants getting up at the same time each morning if possible. This is to minimize in the effect of circadian rhythm on BP, which has been demonstrated in two studies.…”
Section: Cardiovascular End Pointsmentioning
confidence: 99%